2023
DOI: 10.1038/s41598-023-49658-1
|View full text |Cite
|
Sign up to set email alerts
|

Higher systemic immune-inflammation index is associated with sarcopenia in individuals aged 18–59 years: a population-based study

Jinlong Zhao,
Lingfeng Zeng,
Guihong Liang
et al.

Abstract: The association between the systemic immune-inflammation index (SII) and the risk of sarcopenia has not yet been revealed. The purpose of this study was to investigate the relationship between the SII and sarcopenia in individuals aged 18–59 years. All data for this study are from the National Health and Nutrition Examination Survey (NHANES) database, including 7258 participants (age range: 18–59 years). We divided SII values by quartiles (quartiles 1–4: 0.3–3.1, 3.2–4.4, 4.4–6.2, and 6.2–58.5). We constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…4 Significantly different with SARCF + EBM (p < 0.05). 5 Significantly different with Handgrip strength (p < 0.05). 6 Significantly different with Chair stand time (p < 0.05).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…4 Significantly different with SARCF + EBM (p < 0.05). 5 Significantly different with Handgrip strength (p < 0.05). 6 Significantly different with Chair stand time (p < 0.05).…”
Section: Resultsmentioning
confidence: 91%
“…Sarcopenia predominantly affects the elderly; however, younger individuals with chronic diseases are also at risk. The National Health and Nutrition Examination Survey (NHANES) database highlighted that increased systemic immune inflammation escalates the risk of sarcopenia among younger individuals aged 18–59 5 . Therefore, axSpA patients have an elevated risk of developing sarcopenia due to the substantial burden of systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia has been reported to be closely associated with NAFLD. It causes sarcopenia-related obesity, which increases the risk of nonalcoholic steatohepatitis, liver fibrosis, and CVD 44 46 . However, due to the lack of data on sarcopenia status in our patients, we were unable to explore the association of SIIs with sarcopenia in the current study, which is suggested to be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%